The Molecular Role of IL-35 in Non-Small Cell Lung Cancer - Hao, Yuqiu; Dong, Hongna; Li, Wei; Lv, Xuejiao; Shi, Bingqing; Gao, Peng (Frontiers in Oncology, 2022)
Non-small cell lung cancer (NSCLC) is the most common type of lung cancer and a common cause of cancer-related death. Better understanding the molecular mechanisms, pathogenesis, and treatment of NSCLC can help improve patient outcomes. Significant progress has been made in the treatment of NSCLC, and immunotherapy can prolong patient survival. However, the overall cure and survival rates of NSCLC are low, especially in patients with advanced metastases. Interleukin-35 (IL-35)—an immunosuppressive factor associated with the onset and prognosis of various cancers. Studies have shown IL-35 expression is elevated in NSCLC, and it is closely related to the progression and prognosis of NSCLC. However, there are few studies on the mechanism of IL-35 in NSCLC. This study discusses the role of IL-35 and its downstream signaling pathways in the pathogenesis of NSCLC and provides new insights into its therapeutic potential.